2017
DOI: 10.1186/s12888-017-1499-4
|View full text |Cite
|
Sign up to set email alerts
|

Trends in levels of self-reported psychological distress among individuals who seek psychiatric services over eight years: a comparison between age groups in three population surveys in Stockholm County

Abstract: BackgroundPsychiatric service use has increased in Sweden and in other developed countries, particularly among young people. Possible explanations include lower threshold for help-seeking among young people, but evidence is scarce.MethodsWe analysed the 2002, 2006 and 2010 Stockholm public health surveys for changes in the mean level of psychological distress among adult users of psychiatric in- and outpatient services in four age groups: 18–24, 25–44, 45–64 and ≥65 years. Psychological distress was measured v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
23
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(26 citation statements)
references
References 29 publications
3
23
0
Order By: Relevance
“…According to the Norwegian Institute of Public Health [43], underuse of primary healthcare services appears to be more likely in the general population. On the other hand, the Norwegian Institute of Public Health points out that if help-seeking behavior were to increase among those with low levels of psychological symptoms as opposed to those with high levels of symptoms, as seen in our study and in a study by Kosidou et al [13], this might instead indicate overuse of health services.…”
Section: Discussionsupporting
confidence: 45%
See 2 more Smart Citations
“…According to the Norwegian Institute of Public Health [43], underuse of primary healthcare services appears to be more likely in the general population. On the other hand, the Norwegian Institute of Public Health points out that if help-seeking behavior were to increase among those with low levels of psychological symptoms as opposed to those with high levels of symptoms, as seen in our study and in a study by Kosidou et al [13], this might instead indicate overuse of health services.…”
Section: Discussionsupporting
confidence: 45%
“…However, this development was not found among adults. The authors therefore argued that a lower threshold of help-seeking behavior among young people may explain the recent increase in psychiatric service use in Sweden and perhaps in other developed countries [13]. Another study involving patient data from 34 countries investigated the propensity to seek healthcare and found that it was weakly associated with greater use of a family doctor [45].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Symptom Checklist‐90) and Brief Symptom Inventory have been widely used for screening of psychological distress in medical patients and demonstrated high levels of specificity and sensitivity (Carlson & Bultz, ; Zabora, Smith‐Wilson, Fetting, & Enterline, ). The 12‐item General Health Questionnaire (GHQ‐12) is designed to study psychological disorders in general clinical setting and has been used in various studies for distress screening (Cuellar‐Flores, Sánchez‐López, Limiñana‐Gras, & Colodro‐Conde, ; Kosidou et al, ). A popular scale for distress assessment is the K10 (Kessler et al, ).…”
Section: Assessment Scalesmentioning
confidence: 99%
“…The 12-item General Health Questionnaire (GHQ-12) is designed to study psychological disorders in general clinical setting and has been used in various studies for distress screening (Cuellar-Flores, Sánchez-López, Limiñana-Gras, & Colodro-Conde, 2014;Kosidou et al, 2017). A popular scale for distress assessment is the K10(Kessler et al, 2002).…”
mentioning
confidence: 99%